Nyctanthes arbor-tristis Improves Blood Pressure via Endothelial Pathway: In Silico, Ex Vivo, and In Vivo Evidence - Chaturvedi, Akanksha; Verma, Kanika; Jain, Smita; Sharma, Pragya; Paliwal, Vartika; Paliwal, Sarvesh; Sharma, Swapnil (Cell biochemistry and biophysics, 2025)
Systemic hypertension, a common metabolic disorder, poses significant health risks despite the availability of antihypertensive drugs. Nyctanthes arbor-tristis has garnered increasing attention for its perceived efficacy and safety, though its mechanisms of action and the bioactive compounds responsible for its antihypertensive effects remain elusive. Therefore, this study aims to elucidate the antihypertensive activity of N. arbor-tristis leaves in rats and explore associated mechanism through in silico, in vitro, ex vivo, and in vivo studies. The methanolic extract of N. arbor-tristis leaves (MENAT) was fractionated and subjected to qualitative and quantitative phytochemical screening, including total phenolic content (Folin-Ciocalteu method), total flavonoid content (Aluminum chloride method), and total alkaloid content (spectrometric method). Antioxidant studies were conducted using DPPH, FRAP, and H 2 O 2 assays. The most promising fraction (WNAT) was analyzed using LC-MS, and the identified compounds were used for molecular docking studies against cGMP and eNOS. Further, aortic ring assays were conducted to assess ex vivo vasorelaxant activity (rat aortic strip assay) and the underlying mechanisms of WNAT. Later, in vivo studies using a DOCA-salt-induced hypertension model in Wistar rats, along with molecular analyses (RT-PCR), were performed to validate the antihypertensive claims of N. arbor-tristis . In vitro studies demonstrated that the water extract of N. arbor-tristis leaves (WNAT) exhibited strong antioxidant activity and contained key phytochemicals. LC-MS analysis revealed the presence of 19 major compounds, including betulinic acid and arbortristosides. Molecular docking studies indicated that arborside C exhibited a strong affinity for both eNOS and cGMP. Ex vivo studies involving rat aortic strips showed that WNAT induced vasodilatory activity, which is associated with parasympathetic and nitric oxide-related pathways. In vivo experiments further supported WNAT’s antihypertensive properties through improvements via amelioration of rat blood pressure and histological features, biochemical markers, morphometric parameters, and gene expression in hypertensive rats. In conclusion, WNAT effectively lowers blood pressure through modulation of the endothelial pathway and warrants further studies to attain its clinical utility in hypertensive subjects. Graphical Abstract Highlights Nyctanthes arbor-tristis has notable antihypertensive properties. Arborside C exhibits impressive affinity with cGMP and NO. The water fraction of MENAT (WNAT) modulates the levels of the Soluble guanylyl cyclase (sGC) gene in the cardiac tissues of DOCA-salt-induced hypertensive rats.